2021
DOI: 10.1038/s41598-021-93916-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between statin medication and hearing impairment in a national health screening cohort

Abstract: This study aimed to investigate the association of previous stain use with hearing impairment in an adult population. Data from the ≥ 40-year-old population in the Korean National Health Insurance Service Health Screening Cohort were used. The hearing impairment group was classified based on the national registry of hearing-impaired persons. Control participants were randomly selected and matched for age, sex, income, and region of residence. The number of days of statin prescription during the 2 years before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Studies on statins and sensorineural hearing loss have generally found a reduced risk of hearing impairment 27 29 . In a study using national health screening data, the odds ratio of hearing impairment was lower in the statin group, with a more significant effect observed in the hydrophilic statin group 9 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies on statins and sensorineural hearing loss have generally found a reduced risk of hearing impairment 27 29 . In a study using national health screening data, the odds ratio of hearing impairment was lower in the statin group, with a more significant effect observed in the hydrophilic statin group 9 .…”
Section: Discussionmentioning
confidence: 96%
“…Cardiovascular damage and neurodegeneration are known risk factors for hearing loss 6 8 . Statins, which are commonly used to treat cardiovascular and neurological disorders, may also be effective for treating hearing impairment 5 , 9 . Statins are a class of drugs that are commonly used for the treating hyperlipidemia and for preventing heart attack and stroke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, a recent study demonstrated that statins can reduce cisplatin ototoxicity, resulting in improved hearing thresholds after cisplatin treatment 7 . In addition, in a cohort study of a population aged ≥40 years (514,866 individuals), patients with a history of statin treatment showed a significant decrease in the prevalence of hearing impairment among the elderly compared to the non‐statin treatment group 26 . However, the therapeutic effects of statins on ISSNHL in humans have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“… 7 In addition, in a cohort study of a population aged ≥40 years (514,866 individuals), patients with a history of statin treatment showed a significant decrease in the prevalence of hearing impairment among the elderly compared to the non‐statin treatment group. 26 However, the therapeutic effects of statins on ISSNHL in humans have not been investigated. To our knowledge, this is the first study to investigate the effects of statins on hearing prognosis in patients with ISSNHL.…”
Section: Discussionmentioning
confidence: 99%